SNPs in the Toll1 receptor of Litopenaeus vannamei are associated with immune response. Issue 72 (January 2018) - Yao, Defu; Su, Huimin; Zhu, Jinghua; Zhao, Xianliang; Aweya, Jude Juventus; Wang, Fan; Zhong, Mingqi; Zhang, Yueling
Abstract: Tolls and Toll-like receptors (TLRs) are important regulators in the innate immune system and their genetic variations usually affect the host's susceptibility/resistance to pathogen infections. In this study, we report on the single nucleotide polymorphisms (SNPs) of Toll1 in Litopenaeus vannamei (LvToll1) and how this is associated with immune response. PCR-DGGE analysis revealed genetic polymorphisms in LvToll1 at both the genomic DNA (gDNA) and cDNA levels. Using high-throughput sequencing, 223 SNPs were identified at the gDNA level, of which 145 were non-synonymous SNP (nsSNP), with 3 nsSNPs having frequency over 1%. On the other hand, 60 SNPs were identified at the cDNA level including 38 nsSNPs and 4 nsSNPs with frequency over 1%. Upon challenging shrimps with Streptococcus iniae, Vibrio parahaemolyticus and white spot syndrome virus (WSSV), LvToll1 was shown to generate 6, 4 and 4 novel bands, respectively when analyzed with PCR-DGGE. Sequencing analysis of these bands showed that they contained 6, 4 and 2 nsSNPs, respectively. Moreover, the nsSNP C1526T was detected in S. iniae -resistant but not in susceptible shrimps. Most significantly, the C1526T mutation could shorten the α-helix of the LRR domain and was predicted to affect the function of LvToll1, indicating that SNP C1526T might be associated with shrimp's resistance to pathogen infections. In sum, our findings here reveal that the genetic polymorphisms of Toll receptor are linked with the immune response to pathogen infections in L. vannamei . Highlights: We found for the first time that Litopenaeus vannamei Toll1 (LvToll1) possessed extraordinary SNPs. It could be modulated by various pathogen infections. The SNP C1526T might be associated with the shrimp's resistance to infections.